Marmosets treated with oxytocin are more socially attractive to their long-term mate - Cavanaugh, Jon; Huffman, Michelle C.; Harnisch, April M.; French, Jeffrey A. (Frontiers in Behavioral Neuroscience, 2015)
Adult male-female bonds are partly characterized by initiating and maintaining close proximity with a social partner, as well as engaging in high levels of affiliative and sociosexual behavior. Oxytocin (OXT), a neuromodulatory nonapeptide, plays a critical role in the facilitation of social bonding and prosocial behavior toward a social partner (Feldman, 2012). However, less attention has been given to whether augmentation of OXT levels in an individual alters others’ perceptions and behavior toward an OXT-treated social partner. We examined social dynamics in well-established male-female pairs of marmoset monkeys (Callithrix jacchus) in which one member of the pair was administered an intranasal OXT agonist, an OXT antagonist, or saline. OXT treatment did not alter the expression of affiliative toward an untreated partner. However, OXT did significantly influence the expression of proximity and grooming behavior with a treated partner, as a function of OXT treatment and sex. Female interest in initiating and maintaining proximity with a pair-mate was altered by OXT treatment. Untreated female marmosets departed from their saline-treated partner more frequently than they approached them, as indicated by a low proximity index score. However, when males received an intranasal OXT agonist they had a significantly increased proximity index score relative to saline, indicating that their untreated partner approached them more often than they departed from them). Saline-treated females initiated and received equivalent levels of grooming behavior. However, when female marmosets were treated with an OXT agonist their untreated partner groomed them proportionately more often, for a greater total duration, and for more time per bout, than they initiated grooming behavior. These results suggest that intranasal OXT altered male and female marmosets’ stimulus properties in such a way as to increase the amount of grooming behavior that females received from their long-term mate, as well as increase female interest in initiating and maintaining proximity with their long-term mate. Furthermore, these results support the notion that central OXT activity plays an important neuromodulatory role in the maintenance of long-lasting male-female relationships.